LOCAL HYPERTHERMIA IN THE COMBINED TREATMENT OF LOCALLY ADVANCED SOFT TISSUE SARCOMAS - A. L. Zubarev; A. A. Kurilchik; O. K. Kurpeshev; A. L. Starodubtev; V. E. Ivanov (Сибирский онкологический журнал, 2016)
183 patients with locally advanced STS treated in MRRC were analyzed. In group 1 were included 107 patients who received preoperative thermo-chemo-radiotherapy (ТCRТ) and surgery (S). The group 2 consisted of 76 patients treated with preoperative chemo-radiotherapy (CRТ) followed by S too. The locoregional-recurrencefree-survival (LRFS), metastasis-free survival and overall survival rates (93 %, 69 %, 84 %) at 5 years were higher in groups with ТCRТ compared to the CRT (78 %, 56 %, 68 %). Local hyperthermia didn’t increase an incidence of postoperative complications.